The Influence of Social Media Marketing Elements on Brand Loyalty Mediated by Customer Brand Engagement: Case Study of ASUS Laptop Users - Narantaka, Fadhil Farrelian; Abidin, Zaenal (Journal of Advances in Information Systems and Technology, 2023)
This study was conducted to determine the influence of social media marketing elements, namely entertainment, interaction, customisation, electronic word of mouth (E-WOM), and trendiness on brand loyalty mediated by customer brand engagement on Asus laptops. This research was conducted on Universitas Negeri Semarang students with a sample of 396 students. The sampling method used was purposive sampling, which is a sample based on certain criteria, namely students who use Asus laptops. The data collected has been analyzed using structural equation modelling-Partial Least Square (SEM-PLS) with SmartPLS 4 software. The results of the study concluded that entertainment such as increasing Asus laptop video / image content attractively and E-WOM invites consumers to increase their desire to provide information about their experience in using Asus laptops, entertainment and E-WOM have a significant effect on customer brand engagement and customer brand engagement has a significant effect on brand loyalty, for example such as increasing consumer happiness when using Asus laptops by providing the right specifications, attractive appearance, and features that make it easier to use Asus laptops. While interaction, customisation, trendiness do not have a significant effect on customer brand engagement.